Design and simulation of BLDC motor control using MATLAB simulink: A detailed approach - Dwi Sudarno Putra; Wawan Purwanto; Risfendra Risfendra; Joel O. Abratiguin; Agus Baharudin; Thorikul Huda (Universitas Muhammadiyah Magelang, 2025)
Brushless Direct Current (BLDC) motors are increasingly utilized across various applications due to their high efficiency and reliability. However, their control requires precise handling, especially during the commutation process. This study presents a detailed simulation design for BLDC motor control using MATLAB Simulink, focusing on the Six-Step Commutation method and PID-based speed regulation. The methodology involves constructing an open-loop model to analyze commutation behavior, followed by a closed-loop system using PID controllers with automatic parameter tuning. The simulation demonstrates accurate replication of hall sensor signals, back-EMF waveforms, switching patterns, and motor responses. Results reveal that the PID controller effectively maintains target speed across varying reference inputs and load conditions, while phase current and electromagnetic torque increase proportionally with speed and load. Results confirm correct switching in open loop and show that, in closed loop, the controller maintains speed within ±2% of the target with brief, well-damped transients. Phase current and torque responses scale with speed and load, informing practical refinements (anti-windup, ripple mitigation, soft-commutation timing). The findings certify that simulation is a vital step to ensure functional logic and hardware readiness, minimizing risks and enhancing system performance prior to physical implementation.